On the short circuit resilience of organic solar cells: prediction and validation. Issue 33 (7th September 2015) - Jolt Oostra, A.; Smits, Edsger C. P.; de Leeuw, Dago M.; Blom, Paul W. M.; Michels, Jasper J.
<x xml:space="preserve">Abstract</x> As flexible organic solar cell performance suffers from processing-related short-circuits, quantitative insight in the effect of flaws is eminent. This work provides such insight and explains how an intrinsic healing mechanism significantly enhances fault-tolerance.